On Jesus’ Last Week(s) - Nodet, Étienne (Biblica, 2011)
Five conclusions allow us to explain Jesus last days and to assess the significance of the actual Gospel narratives. Firstly, his last Passover meal (Synoptics, solar calendar) took place on one Tuesday evening; secondly, the origin of the Eucharistic rite on the Lord’s day has nothing to do with Passover; thirdly, a feast of Passover-Easter (Pa/sxa) on a specific Sunday emerged somewhat late in the IInd century; fourthly, before this date, the Synoptics did not have their final shape; fifthly Josephus provides us with a clue to understand Jesus’ double trial before Pilate in the Passion narrative of John.